Fabrication of AlGaN nanostructures by nanolithography on ultraviolet LEDs grown on Si substrates. (19th February 2019) - Ma, Chuanfei; Feng, Meixin; Wang, Jin; Zhou, Rui; Sun, Qian; Liu, Jianxun; Huang, Yingnan; Gao, Hongwei; Zhou, Yu; Yang, Hui
Abstract: AlGaN nanostructures have many applications because of their interesting and unique properties. Here we report a simple fabrication method of AlGaN nanostructures by nanolithography on ultraviolet (UV) LEDs grown on Si substrates. We also studied the effects of various AlGaN nanostructure arrays on the performance of the UV (370 nm) thin-film LEDs with an embedded n-type contact. The output power of the UV LEDs with nanostructures was enhanced by 3.9 times compared to the flat UV LEDs, while no penalty was induced for the electrical characteristics of the UV LEDs. Additionally, the far-field radiation pattern of the UV LEDs with nanostructures showed much better directionality and a much stronger intensity than the flat UV LEDs, which would be of great benefit to directional UV curing applications.